Efficacy of repeated peripheral magnetic stimulation on upper limb motor function after stroke: a systematic review and meta-analysis of randomized controlled trials - Liao, Defu; He, Ziyan; Yan, Shichang; Ji, Qipei; Li, Yuanlin; Tu, Yuyuan; Zhou, Zihao; Ai, Shuangchun (Frontiers in Neurology, 2025)
BackgroundPost-stroke patients with upper motor neuron lesions have limited motor function in the upper limbs, and spasticity occurs in the limbs, thus affecting functional recovery and activities of daily living. Repetitive peripheral magnetic stimulation (rPMS) is a non-invasive treatment often used in clinical rehabilitation. Recent studies have shown that it can reduce spasticity and improve motor function in patients.ObjectiveThis study aimed to evaluate the effectiveness of rPMS on upper limb motor function and spasticity in stroke patients by meta-analysis.Materials and methodsRandomized controlled trials (RCTs) of rPMS in post-stroke patients were searched in PubMed, Embase, Cochrane Library, Web of Science, and Clinical Trials. Databases from the date of creation to 25 August 2024 were evaluated using the Cochrane Collaboration tool. Methodological quality was assessed using the Cochrane Collaboration tools, and meta-analyses were performed using RevMan (version 5.4) and Stata (version 14.0).ResultsA total of 8 studies were included. RPMS improved patients’ FMA-UE scores compared with controls (MD = 3.34, 95% CI = [0.53, 6.15], p = 0.02 < 0.05). RPMS also reduced spasticity (MD = −0.66, 95% CI = [−1.16, −0.15], p = 0.01 < 0.05) and increased patients’ ability to live independently (MD = 0.85, 95% CI = [0.19, 1.51], p = 0.01 < 0.05). Subgroup analyses showed that the efficacy of treatment frequency ≤ 20 Hz was better than that of frequency > 20 Hz; the treatment time using 15–20 min was more effective than using 30 min; and the application of round coil treatment was more effective than other types of coils.ConclusionThe results suggest that if rPMS is used in post-stroke patients, their upper limb motor function and spasticity may improve. However, the number of studies is small, and further research is needed to extend the current analysis results.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, CRD42024584040.